Use of complete blood count for predicting preterm birth in asymptomatic pregnant women: A propensity score‐matched analysis. Issue 8 (27th March 2020) - Ma, Mei; Zhu, Mei; Zhuo, Bimin; Li, Li; Chen, Honglei; Xu, Libo; Wu, Zhihui; Cheng, Feng; Xu, Liangpu; Yan, Jianying
Abstract: Background: Accurate prediction of preterm birth (PTB) is still difficult, mostly because of the multifactorial etiology of PTB. Previous studies have been mostly focused on the prediction of PTB in symptomatic women or those presenting with threatened preterm labor. We aimed to study whether complete blood count (CBC) parameters at 20‐30 weeks of pregnancy can predict asymptomatic PTB. Methods: In this retrospective case‐control study, the preterm and term delivery groups were matched by propensity score‐matched (PSM) analysis. Baseline data and the CBC parameters examined at 20‐30 weeks of gestation were recorded. Results: The combined marker of neutrophil‐to‐lymphocyte ratio (NLR), hemoglobin (HGB), and platelet distribution width (PDW) accurately predicts PTB at a cutoff value of 0.25, with sensitivity and specificity of 88.6% and 40.5% and negative and positive predictive value of 97.9% and 10.2%, respectively. Conclusion: The combined marker of CBC parameters can supplement other markers to predict PTB about 10 weeks in advance. This combined marker had a very high negative predictive value for PTB. Therefore, in subjects with normal combined marker value, further screening tests for PTB may be eliminated unless clinical suspicion is high.